Theoretical Bases of the Compatible Work of the Constraction of Stormwater Drainage Systems in the Regulation of Stormwater Runoff - Tkachuk, Olexander; Yaruta, Yana; Shevchuk, Yaruta; Azizova, Anna (International Journal of Engineering and Technology, 2018)
Measures of flooding process on urban areas, urban stormwater sewerage systems and methods regulation of stormwater need to be rectification. The method of temporary interception stormwater at places of their precipitation with infiltration basins is reviewed. Infiltration basins are used to reduce the peak load on existing stormwater sewerage facilities, prevent the causes of flooding by stormwater. The processes of stormwater formation on urban areas is analyzed. Analytical dependencies for the hydrograph construction of flow through sewers and their inflow to the accumulation points were obtained. Conditions for the regulation of stormwater on urban areas with its partial flow and temporary interception on infiltration basins are determined. A refined exponent formula with a coefficient taking into account the filling of the pipeline for hydraulic and optimization calculations of pressure and non-pressure sewerage pipelines are proposed. Numerical values of coefficients and exponent of the specified formula for Ukrainian normative indicators of working conditions and calculations of sewerage pipelines are obtained. The full expediency of the refined power formula for practical use has been confirmed. The application of this formula for calculations of the compatible work of the pipelines and joint operation with the stormwater regulating construction to calculate the work of sewerage networks in the pressure and non-pressure conditions and identify possible areas of flooding with location of infiltration basins there. Â Â Â